Berkeley at War : the 1960s. - Rorabaugh, W. J. (Oxford University Press, 2006)
Berkeley, California stood at the center of the political, social, and cultural upheaval that made the 1960s a unique period in American history. In Berkeley at War, W.J. Rorabaugh, who attended the graduate school of the University of California at Berkeley in the 1970s, presents alively, informative account of the events that changed forever what had once been a quiet, conservative white suburb. Rorabaugh's meticulously researched, authoritative narrative covers the entire period, from the rise of the Free Speech Movement to the growth and increasing militance of a black community strugg.